Socio‐psychological factors, beyond knowledge, predict people's engagement in pollinator conservation. Issue 1 (19th November 2020) - Knapp, Jessica L.; Phillips, Benjamin B.; Clements, Jen; Shaw, Rosalind F.; Osborne, Juliet L.
Abstract: Nature conservation often depends on the behaviour of individuals, which can be driven by socio‐psychological factors such as a person's attitude, knowledge and identity. Despite extensive ecological research about pollinator declines, there has been almost no social research assessing the drivers of people's engagement in pollinator conservation. To address this gap, we used a large‐scale, online questionnaire in the United Kingdom, broadly framed around the Theory of Planned Behaviour. We received a total of 1, 275 responses from a wide range of ages, incomes and education levels, despite a selection bias towards people with a pre‐existing interest in pollinators. A range of socio‐psychological factors predicted people's pollinator conservation actions and explained 45% of the variation. Respondents' diversity of nature interactions and perceived behavioural control (feeling able to help pollinators) were consistently important predictors of people's pollinator conservation actions, whilst the importance of other socio‐psychological factors depended on the particular action. Notably, knowledge was far less important overall than people's perceptions and other socio‐psychological factors, highlighting a knowledge‐action gap. Further unexplained variation in people's behaviour could partly be due by structural and contextual factors, particularly regarding social norms around tidiness. From a practical perspective, our findings reveal three main insights. First, several simple, low‐cost pollinator conservation actions (reduced mowing, leaving areas unmown and creating patches of bare ground for ground‐nesting bees) are currently under‐utilised so should be priorities for pollinator conservation programmes. Second, strategies are needed to overcome reported practical barriers, for example by providing free resources (e.g. seeds of pollen‐ and nectar‐rich plants) and communicating simple beneficial actions that can be carried out with limited time, space and money. Third, knowledge is just one (relatively less important) factor that predicts pollinator conservation behaviour—other socio‐psychological factors provide potential pathways for increasing uptake, and structural and contextual limitations also need to be considered. In practice, this could be achieved by engaging, inspiring and empowering the public to help pollinators and to take responsibility for their local environment, for example through environmental education and community programmes facilitating public interest and involvement in the management of greenspace. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.